Survey of ICT and Education in Africa : Lesotho Country Report - Isaacs, Shafika (World Bank, Washington, DC, 2012)
This short country report, a result of larger Information for Development Program (infoDev) - supported survey of the Information and Communication Technologies (ICT) in education in Africa, provides a general overview of current activities and issues related to ICT use in education in the country. Despite its poor ICT infrastructure and high levels of poverty, Lesotho has begun to take the necessary steps to promote higher levels of ICT access and usage in its communities and education institutions. The Government of Lesotho has adopted a national ICT policy that makes some references to the education sector. Over the last two years, the New Partnership for Africa's Development (NEPAD) eSchools Demo Project in Lesotho has been a catalyst in focusing attention on the potential that ICTs hold to enhance education in the country.